The Influence of Organizational Culture, Teacher Performance, and Teacher Competence on the Quality of Education at MTs. Putra Nurul Hakim, Kediri District - Hamka, Hamka; Hakim, Lukman; Thohri, Muhammad (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2023)
This study investigates how organizational culture, teacher performance, and teacher competence influence education quality at MTs. Putra Nurul Hakim, Kediri District, using a quantitative approach with multiple linear regression analysis. Data from 67 teachers and 104 students, gathered through questionnaires, reveal that organizational culture, teacher performance, and teacher competence significantly affect education quality. MTs. Putra Nurul Hakim fosters a supportive culture, fostering student achievement, satisfaction, and teacher motivation. Good teacher performance, evidenced by teaching skills and curriculum development, positively impacts student achievement, satisfaction, motivation, and interest. Teacher competence, including qualifications and pedagogical knowledge, also significantly affects education quality. Recommendations include developing training programs, transparent performance assessments, and long-term strategic plans to enhance education quality. Collaboration with external parties is proposed to support quality improvement efforts. Implementing these recommendations is expected to continuously enhance education quality at MTs. Putra Nurul Hakim, producing competent graduates ready for future challenges.